Analysis of grip force during golf putting at different distances - pilot study - Wang, Y.-T.; Su, P.-C.; Wu, Y.-L.; Chang, J.-H. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to explore the grip force performance at different distances during putting stroke. Four golfers (2 professionals and 2 novices) as accurately as possible executed a putt to reach 1, 2 and 3 m target distance, respectively. Putting motions were recorded by JVC video and grip pressure measurement sensor placed on two hands, allowing the force output of all regions of the hands to be measured. The grip force trace among 1 to 3 m distance was repeatable across putting strokes for each golfer but between golfers was inconsistent. Dominant forces appear to arise primarily from the left hand. In this study, the grip force and force distribution were preliminarily discovered during putting stroke at different distances. This research has suggested a potentially important influence of grip force on the golf putting performance in long distance.